Placental inflammation is increased in gestational diabetes mellitus: The role of inflammasome NLRP-3 and chemokine scavenger decoy receptor D6. - Marianna Onori; Giuliana Beneduce; Filomena Colella; Donatella Lucchetti; Caterina Policola; Vincenzo Arena; Fabio Sannino; Alessandro Petrecca; Dario Pitocco; Alfredo Pontecorvi; Alessandro Sgambato; Giovanni Scambia; et al. (PLoS ONE)
Background Gestational diabetes mellitus is characterized by low-grade systemic inflammation. Placental inflammation in gestation diabetes mellitus has not been extensively investigated yet. Objectives Aims of this study were to analyze: a) serum levels of Th-1 cytokines and D6-specific chemokines in women with gestation diabetes mellitus, compared to normal pregnant women; b) placental expression of the inflammasome NLR family pyrin domain containing 3 (NLRP-3) and the chemokines scavenger decoy D6 receptor. Methods Serum samples collected between 24 and 28 weeks of pregnancy from singleton pregnancies with gestational diabetes mellitus and gestational age-matched normal pregnant women were analyzed by bead-based multiplex assays for chemokine (C-C motif) ligand 2 (CCL2), chemokine (C-C motif) ligand 4 (CCL4), interferon gamma (IFN-γ), C-C motif chemokine ligand 11 (CCL11) and tumor necrosis factor alpha (TNF-α) levels. Placental samples from GDM and controls were analysed by immunohistochemistry and multiplex spatial immunofluorescence for protein expression of NLR family pyrin domain containing 3 (NLRP-3), interleukin-1 beta (IL-1β) and chemokines scavenger decoy D6 receptor. Results GDM women (n = 25) showed higher serum levels of CCL-2 (p < 0.01), CCL-4 (p < 0.05) and IFN-γ (p < 0.05) compared to controls (n = 25). Placental expression of NLRP-3 was significantly higher in GDM women (n = 10) compared to controls (n = 7; p < 0.05) while only a trend of increase of IL-1β and D6 expression was observed in GDM compared to normal placentas. Conclusions GDM is characterized by higher serum levels of pro-inflammatory cytokines with consistent over-expression of the inflammasome NLRP-3 in placental tissues compared to normal pregnancy.